Physicochemical and sensory characteristics of bovine and goat kefir with strawberry flavor - Chacón-Villalobos, Alejandro (2025)
This study, conducted in San Pedro, Montes de Oca, Costa Rica, aimed to evaluate the impact of different proportions of goat and bovine milk on the characteristics of strawberry kefir through physicochemical, microbiological, and sensory analyses. Five milk combinations were tested to assess their influence on the final product. Measurements were taken on days 1 and 7 to determine the effect of the different proportions over storage time. Variables such as pH, total acidity, viscosity, syneresis percentage, alcohol content, color, thermotolerant coliforms (TC), and yeasts were analyzed. A sensory test was carried out with 104 participants who evaluated the five proposed formulations and a commercial kefir sample. The highest alcohol content, viscosity, and color values were obtained in the kefir made exclusively with bovine milk, while the greatest syneresis occurred in the kefir produced only with goat milk. Yeast counts remained within acceptable limits in all formulations, and TC presence was minimal. Interactions between formulations and storage time were observed for pH, titratable acidity, and viscosity. The sensory evaluation showed that the commercial kefir received the lowest acceptance. Among the proposed formulations, the kefir made with 100% goat milk was the least preferred, while the formulation containing 25% goat milk had the highest acceptance. Specifically, the strawberry-flavored kefir with 25% goat milk was selected due to its superior sensory characteristics and showed the second-best physicochemical performance, surpassed only by the bovine milk formulation. Therefore, the inclusion of goat milk allows the production of kefir with acceptable physicochemical and sensory properties.